Enantioselective monitoring of chiral fungicide famoxadone enantiomers in tomato, apple, and grape by chiral liquid chromatography with tandem mass spectrometry. Issue 20 (10th September 2018) - Xu, Guofeng; Jia, Xiaohui; Wu, Xiaohu; Xu, Jun; Liu, Xingang; Pan, Xinglu; Li, Runan; Li, Xinghai; Dong, Fengshou
Abstract: Famoxadone is a widely used chiral fungicide on tomato, apple, and grape. But it is still being employed as a racemic mixture without distinguishing the difference between enantiomers, which often leads to its inaccurate risk assessment. In this study, a rapid, sensitive, and reliable chiral analytical method was developed for famoxadone enantiomers by ultra high performance liquid chromatography/tandem mass spectrometry, optimal separation condition was achieved with Lux Amylose‐1 column using acetonitrile/water (70:30, v/v) as mobile phase at 0.3 mL/min in 6 min. The average recoveries for two enantiomers in all of the matrices at three spiking levels ranged from 89.8 to 109.4%, with relative standard deviation less than 9.5%. The limits of quantification for all enantiomers in tomato, apple, and grape were not more than 4 μg/kg. And the proposed method was successfully applied to investigate the enantioselective degradation of famoxadone enantiomers in tomato, apple, and grape. The data showed that S ‐(+)‐famoxadone was preferentially degraded comparing to the R ‐(−)‐famoxadone in tomato, apple, and grape. The potential reasons of the enantioselective behavior were also discussed. This study could help in better understanding the environmental fate of famoxadone and the rational use of chiral pesticide in agricultural production.